2003
DOI: 10.1080/0003942031000107299
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation with oregano essential oil on performance of broilers after experimental infection witheimeria tenella

Abstract: A study was carried out to examine the effect of dietary supplementation of oregano essential oil on performance of broiler chickens experimentally infected with Eimeria tenella at 14 days of age. A total of 120 day-old Cobb-500 chicks separated into 4 equal groups with three replicates each, were used in this study. Two groups, one infected with 5 x 10(4) sporulated oocysts of E. tenella and the other not, were given a basal diet and served as controls. The other two groups also infected with E. tenella were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
145
0
23

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(178 citation statements)
references
References 24 publications
10
145
0
23
Order By: Relevance
“…Corino et al (2007b) conducted a similar study on piglets in post-weaning; piglets were fed with a concentrate that was supplemented with two levels of VB, and the authors found considerable growth improvement in the subjects that were fed the highest level of VB. The beneficial effect of phenols and polyphenols can be ascribed, according to some authors (Giannenas et al, 2003;ArcilaLozano et al, 2004;Bozin et al, 2006), to the antimicrobial and antifungal activity inherent in phenolic compounds. Other authors (Esposito et al, 2010;Rossi et al, 2011) have attributed that effect to the anti-inflammatory and immunomodulating activity of phenol compounds.…”
Section: Productive Performancementioning
confidence: 99%
“…Corino et al (2007b) conducted a similar study on piglets in post-weaning; piglets were fed with a concentrate that was supplemented with two levels of VB, and the authors found considerable growth improvement in the subjects that were fed the highest level of VB. The beneficial effect of phenols and polyphenols can be ascribed, according to some authors (Giannenas et al, 2003;ArcilaLozano et al, 2004;Bozin et al, 2006), to the antimicrobial and antifungal activity inherent in phenolic compounds. Other authors (Esposito et al, 2010;Rossi et al, 2011) have attributed that effect to the anti-inflammatory and immunomodulating activity of phenol compounds.…”
Section: Productive Performancementioning
confidence: 99%
“…Para a quantidade total de oocistos excretados no período acumulado de 4 a 7 dias, os menores valores foram observados para os 4,00 3,67 3,67 3,67 1,33 0,33 0,33 0,00 DC+Vacina 2 3,67 3,00 2,67 1,67 0,33 0,33 0,00 0,00 AMD/AC 3 3,33 3,33 2,33 2,33 0,33 0,33 0,33 0,00 Gln/Glu 4 4,00 4,00 3,67 1,00 0,00 0,00 0,00 0,00 AFs 5 3,67 3,33 3,67 2,00 0,67 0,33 0,33 0,00 Gln/Glu+AFs 3,67 3,00 3,00 2,00 0,33 0,00 0,00 0,00 CV (%) 4,00 3,67 3,67 3,67 1,33 0,33 0,33 0,00 P 0,538 0,758 0,214 0,058 0,353 0,948 0,909 1,000 Um dos principais efeitos fisiológicos dos diferentes AFs que tem sido relatado em aves é a sua ação antibacteriana e anticoccidiana. Frente ao desafio com coccidiose, alguns pesquisadores relataram diminuição na contagem de oocistos e escores de lesão no epitélio intestinal de aves alimentadas com dieta suplementada com AFs em relação à aves alimentadas com dieta sem suplementação (Evans et al 2001, Giannenas et al 2003, Christaki et al 2004, Yi et al 2005, inclusive em relação às aves alimentadas com dieta contendo antibiótico melhorador de desempenho e anticoccidianos (Miguel et al 2009). Neste estudo, o menor número de oocistos excretados nas fezes foi observado nos tratamentos contendo AFs seguidos do contendo AMD/AC, confirmando os efeitos benéficos dos AFs no controle da coccidiose.…”
Section: Escores De Lesão Do Epitélio Intestinal E Contagem De Oocistosunclassified
“…Já os aditivos fitogênicos vêm sendo estudados como suplementos eficazes na redução de infecções tanto por bacté-rias quanto por Eimerias sp. (Evans et al 2001, Giannenas et al 2003, Christaki et al 2004, Jamroz et al 2005, Miguel et al 2009, Vasconcelos et al 2010.…”
Section: Histomorfometria Da Mucosa Intestinalunclassified
See 1 more Smart Citation
“…Entre estes mecanimos tem-se a barreira epitelial mucosa, fagócitos e outros leucócitos, citocinas e componentes do sistema complemento (YUN et al, 2000). Todavia, o principal meio de controle da doença é através do uso de drogas anticoccidianas, associada com vacinas vivas atenuadas (VELKERS et al, 2010 GIANNENAS et al, 2003;NAIDOO et al, 2008;LEE et al, 2011;ALMEIDA et al, 2012;KIM et al, 2013 O produto utilizado contendo o β-ácido possui concentração de 30%, ou seja, para obter a dosagem de β-ácido especificado utilizou-se 100, 200, 400 e 800 mg/kg do produto para os tratamentos 3, 4, 5 e 6, respectivamente. As concentrações totais de β-ácido detectado nas dietas experimentais estão apresentadas na Tabela 2.…”
Section: Palavrasunclassified